(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
The present study was conducted in Malwa region of Punjab over a period of three years from 2008 to 2010. During this period a total of 1905 dead bodies were brought for post-mortem examination, out of which 156 were unknown bodies representing 8.19% of the total medico legal autopsies, with the rate of 2.7 unknown bodies per 100,000 population per year. Male (87.2%) predominance was seen in unknown bodies with male female ratio of 6.8:1. The most common cause of death among these was starvation (25%), road traffic accidents (21.8%), railway accidents (8.3%).About 8.3% of the bodies were putrefied beyond recognition and no other cause of death was apparent. Most of the unknown dead bodies were between the ages of 11 and 60 years with peak at 21-30 years (33.3%) followed by 31-40 years (23.7%). 86.5% of the unknown dead bodies were recovered before 72 hours and only in 13.5% cases the time since death was more than 72 hours at recovery.